Digital Media vs. Conventional Media: Effectiveness of Learning in Primary Education - Irfa'i Alfian Mubaidilla (Institut Agama Islam Negeri Palopo, 2025)
The rapid development of information technology has transformed learning practices in elementary schools, shifting from predominantly conventional media to increased integration of digital media. This study comparatively analyzes the effectiveness of digital and conventional media in supporting elementary education. The research method employed in this study is the Systematic Literature Review (SLR), with data sources obtained through an article search on Google Scholar within the publication range of 2015-2025., restricted to SINTA indexed journal articles relevant to the topic. Thematic analysis identified the strengths, weaknesses, and integration potential of both media types. Findings reveal that digital media excel in delivering interactive, flexible, and visually engaging learning experiences, enhancing students’ motivation and participation. Conversely, conventional media are more effective in fostering face to face interaction, social skills, and concrete learning experiences aligned with elementary learners’ developmental stages. The study concludes that a strategic combination of digital and conventional media can optimize learning outcomes when adapted to learning objectives, student characteristics, and teacher competencies. The findings offer practical implications for educators and policymakers to design adaptive and context-specific learning strategies in the era of educational transformation.